A field investigation of the effects of drinking consequences on young adults' readiness to change. (February 2015) - Usala, Julie M.; Celio, Mark A.; Lisman, Stephen A.; Day, Anne M.; Spear, Linda P.
Abstract: In the research on readiness to change (RTC) one's drinking, there has been little assessment of the influence of positive drinking consequences or other potential moderating variables. To address these limitations, we examined how young adults' RTC their alcohol consumption shortly following a drinking episode was associated with self-reported drinking consequences, as well as any potential moderating effects of gender and Breath Alcohol Concentration (BrAC). In street interviews outside bars, 238 young adults were administered questionnaires about their drinking, including a measure examining participants' current readiness to reduce their alcohol consumption. Within 72 h of their drinking episode, 67 participants (36 males; entire sample M age  = 20.90 years, Range = 18–26 years) completed an online survey, once again measuring RTC as well as positive and negative drinking consequences. Consistent with our hypothesis, positive drinking consequences were negatively associated with participants' changes in RTC. Additionally, a three-way interaction of gender × BrAC × positive drinking consequences on RTC showed that females with low BrACs reported higher RTC scores when they had endorsed fewer positive drinking consequences. Interestingly, negative drinking consequences alone did not impact individuals' RTC. Because positive drinking consequences were a significantly better predictor of RTC than were negative drinking consequences, researchers are advised to examine both types of consequences in future studies. Finally, effective alcohol education programs for those who have never consumed alcohol as well as social drinkers should include consideration of the experience of positive outcomes. Highlights: A field study examined young adults' readiness to change (RTC) their alcohol use. Positive drinking consequences were negatively associated with RTC. Negative drinking consequences alone did not impact individuals' RTC. Positive consequences are a better predictor of RTC than negative consequences. Positive and negative drinking consequences should be examined in future studies.